Open water characteristics of marine propeller with superhydrophobic surfaces. (1st February 2023) - Chen, Lie; Wang, Shun; Ding, Jiangming; Wang, Yutao; Bennett, Peter; Cheng, Jian; Yang, Qibiao; Liu, Dun
Abstract: In this study, two superhydrophobic blade surfaces of propellers were prepared using nanosecond laser processing and superhydrophobic coating. Numerical calculations of the open water characteristics indicated that superhydrophobic propellers provide higher efficiency over the entire range of operating conditions. Towing tank tests showed that superhydrophobic propellers generate greater thrust but require more torque from an advanced coefficient of 0.3. The increased thrust was caused by the increased pressure differential between the pressure and suction sides. The change in torque was mainly attributed to the gradual loss of the air layer and the increased shape resistance of the rough structure. Within an advance coefficient of 0.3, the laser-processed superhydrophobic propeller exhibited a more apparent drag reduction effect, and the efficiency was improved by a maximum of approximately 2.8%. In contrast, the propeller with superhydrophobic coating has a stable drag reduction effect owing to the stable air layer on its surface during the entire testing process, with an average efficiency improvement of approximately 2.0%. The results confirmed that the superhydrophobic surface, especially the rough structure, significantly affected propeller efficiency. This research extends the practical engineering applications of superhydrophobic surfaces in vessel propulsion. Highlights: Superhydrophobic propeller surfaces were prepared by laser processing and coating. Propeller with laser-processed blades performs well at low advance coefficients. Propeller with coated blades has a good improvement of open water efficiency. The superhydrophobic surface roughness has a significant effect on drag reduction. Reasonable rough structure is beneficial to decrease the turbulence resistance.